Human and Technological Progress Towards the Socio-Economic Paradigm of the Future, Part 2 - Alpidovskaya, Marina; Popkova, Elena G. (Interdisciplinary Thought of the 21st Century ;, 2020)
This book develops a socio-economic paradigm of the future in the context of digital transformation. The challenge of economic openness is considered through the globalization of the world economic system by the example of modern Russia. The tendency of archaization of socio-economic relations is explored which is connected with the gradual disappearance of ineffective institutes and their replacement by new institutes. Attention is paid to the regional aspect of the digital economy - perspectives of development of the ethno-economy in the context of integration of regional economic systems are determined. The problem of preserving social identity and supporting the uniqueness of competitive advantages of the region's economy in the conditions of digitization is actualized, and its perspective solutions based on a region's globalization management are offered. Also, the problem of national and regional food security is considered. Increased social significance of the agro-industrial complex and the necessity for its de-economization on the platform of the digital economy are substantiated. A new concept of the market economy in the conditions of digitization and the Fourth industrial revolution is developed; economic power of technological progress and possibilities of managing and re-directing this power are determined. The authors substantiate the transition to the Sixth technological mode and the related transformation processes in the economy. Also, the authors dwell on the problem of the shadow economy and corruption and consider the perspectives of its overcoming based on the possibilities of digital technologies. The idea of de-regulation based on the possibilities of automatization and AI is opposed to the idea of increase of state regulation based on ubiquitous computing and digital monitoring of economic activities. The perspectives of increasing the economy's transparency in the digital age are proved. The alternatives to the current model of development of the digital economy are given, and scenario analysis of consequences of observing these models based on the cognitive approach is performed. New opportunities for development of the integration processes in entrepreneurship in the conditions of the digital economy are shown - in particular, in the aspect of inter-regional and transnational sectorial clustering. Clusters are considered as growth points of the Russian economy, and the new Russian experience of formation and development of clusters in the sphere of higher education in the context of region's economy is studied. The authors determine the contribution of key technological events in the development of entrepreneurship through the example of modern Russia. They come to the conclusion that despite the unique possibilities digital technologies do not necessarily create additional value for entrepreneurship, and their application could be ineffective due to additional capital expenditures in case of complexity of return of long-term venture investments. The needs of entrepreneurship for innovative infrastructural provision in the context of the digital economy are determined, and barriers on the path of its creation and practical application due to necessity for applying new forms of business organization are shown. Specific features of state management of a region's economy in the conditions of digital modernization are shown, and the modern Russian practice of e-government as a response to the modern challenges is studied. The authors outline new perspectives of development of public-private partnership as an effective direction of industrial and cluster policy of a modern region.